2020
DOI: 10.1177/0954407020916989
|View full text |Cite
|
Sign up to set email alerts
|

Biodiesel/butanol blends as a pure biofuel excluding fossil fuels: Effects on diesel engine combustion, performance, and emission characteristics

Abstract: Although both biodiesel and n-butanol are excellent renewable biofuels, most of the existing research works merely use them as the additives for petroleum diesel. As the main fuel properties of biodiesel and n-butanol are complementary, the biodiesel/ n-butanol blends are promising to be a pure biomass-based substitute for diesel fuel. In this paper, the application of the biodiesel/ n-butanol blends on an agricultural diesel engine was comprehensively investigated, in terms of the combustion, performance, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 50 publications
3
18
0
Order By: Relevance
“…This is because NO x generation is mainly influenced by the oxygen content, duration of combustion, and cylinder temperature. At low loads, the cylinder temperature is low, which is not conducive to NO x production 40 . As the engine load continues to rise, the cylinder temperature rises and the combustion duration is long, resulting in a higher NO x emission.…”
Section: Resultsmentioning
confidence: 99%
“…This is because NO x generation is mainly influenced by the oxygen content, duration of combustion, and cylinder temperature. At low loads, the cylinder temperature is low, which is not conducive to NO x production 40 . As the engine load continues to rise, the cylinder temperature rises and the combustion duration is long, resulting in a higher NO x emission.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the addition of n‐butanol with blends (D50CBD50nBu10 and D50CBD50nBu20) showed lower HRR as compared to diesel owing to 50% blending of biodiesel, lower CN, and higher latent heat of butanol. In general, HRR increased, while butanol was added with biodiesel as examined by Huang et al 113 Authors have analyzed the influence of 10%, 20%, and 30% butanol by volume with neat biodiesel on the diesel engine parameters. It investigated that as n‐butanol blending with biodiesel increased, higher HRR was obtained.…”
Section: Comparison On Influence Of Bu/b Bu/b/d and B/d On Diesel Eng...mentioning
confidence: 99%
“…Longer combustion duration directly affects the BTE of the engine 131 . Huang et al 113 have investigated the effect of n‐butanol (10%, 20%, 30% volume basis) with biodiesel on the combustion, performance, and emissions parameters of the diesel engine. They observed that ignition delay was prolonged with the adding of n‐butanol with biodiesel at all engine loads when the engine worked on two different engine speeds (1600 and 2000 rpm).…”
Section: Comparison On Influence Of Bu/b Bu/b/d and B/d On Diesel Eng...mentioning
confidence: 99%
See 1 more Smart Citation
“…Early studies have found that oxygen has a direct and significant effect on the in-cylinder combustion process. Therefore, increasing the oxygen content of the intake gas can improve the combustion efficiency and reduce fuel consumption and pollutant emissions such as HC, PM, and CO. , Moreover, the activation atmosphere produced by adding oxygen is conducive to the combustion of the mixed gas, which is beneficial to alleviating the problem of narrow load range when the engine is fueled with the n -butanol/diesel-blended fuel. In the early days, due to the limitation of the cost for oxygen-enriched technology, oxygen-enriched combustion was mainly used in the field of thermal power generation.…”
Section: Introductionmentioning
confidence: 99%